The Hidden Dangers: E-Cigarettes, Heated Tobacco, and Their Impact on Oxidative Stress and Atherosclerosis-A Systematic Review and Narrative Synthesis of the Evidence - Arianna Magna; Nausica Polisena; Ludovica Polisena; Chiara Bagnato; Elena Pacella; Roberto Carnevale; Cristina Nocella; Lorenzo Loffredo (MDPI AG, 2024)
Electronic cigarettes and heated tobacco products have seen significant growth in sales and usage in recent years. Initially promoted as potentially less harmful alternatives to traditional tobacco, recent scientific evidence has raised serious concerns about the risks they pose, particularly in relation to atherosclerosis. While atherosclerosis has long been associated with conventional tobacco smoking, emerging research suggests that electronic cigarettes and heated tobacco may also contribute to the development of this condition and related cardiovascular complications. In a narrative review, we examined the potential effects of heated tobacco products and electronic cigarettes on oxidative stress and atherosclerosis. Several studies have shown that e-cigarettes and heated tobacco increase oxidative stress through the activation of enzymes such as NADPH oxidase. One of the primary effects of these products is their pro-thrombotic and pro-atherosclerotic impact on endothelial cells and platelets, which promotes inflammatory processes within the arteries. Furthermore, the chemicals found in electronic cigarette liquids may exacerbate inflammation and cause endothelial dysfunction. Furthermore, through a systematic review, we analyzed the effects of chronic exposure to electronic and heated tobacco cigarettes on endothelial function, as assessed by brachial flow-mediated dilation (FMD). Although electronic cigarettes and heated tobacco cigarettes are often perceived as safer alternatives to traditional smoking, they could still present risks to cardiovascular health. It is essential to raise public awareness about the potential dangers associated with these products and implement protective measures, particularly for young people.